Smart Multi-Agent Framework for Automated Audio Testing - Kovacevic, Jelena; Radujko, Uros; Djukic, Miodrag; Novkovic, Teodora (Elektronika ir Elektrotechnika, 2023)
With the widespread use of embedded software in consumer electronics, automotive industry, medical devices, and industrial environments, embedded software testing is gaining significance as an indispensable part of development and deployment of embedded products. With more than 20 years of research, development, and testing of various consumer technologies and products based on digital signal processors (DSPs) and advanced reduced instruction set computers (ARMs), we obtained insight into typical embedded development process and testing, and the pros and cons of various testing approaches and environments. In this paper, we propose the Smart Multi-Agent Framework based on IoT and Jenkins agents, customised for audio technologies in the Home Audio domain. We evaluated our solution on several complex immersive audio technologies implemented on a multicore DSP. Our uniform, customised, fully automated approach proved to be time efficient, error resilient, easy to replicate and use across all development, certification, and deployment phases of the product life cycle.